Do multiple origins of domestication matter for Amazon Forest? - Thomas, E. (American Association for the Advancement of Science, 2017)
Response to Levis et al. Persistent effects of pre-Columbian plant domestication on Amazonian forest composition, Science 03 Mar 2017: Vol. 355, Issue 6328, pp. 925-931